Health Ministry's Scholarship Policy: Fulfilling Staffing Needs for Doctors and Dentists - Kharisma, Farid; Darmawan, Ede Surya (Poltekita: Jurnal Ilmu Kesehatan, 2025)
Indonesia faces a critical shortage and maldistribution of medical professionals, particularly in Disadvantaged, Border, and Outermost (DTPK) regions. This study analyzes the effectiveness of the Ministry of Health's Educational Funding Assistance Program (Bandikdok) within the new regulatory framework of Law No. 17 of 2023. A qualitative Document and Policy Analysis was conducted. Data were collected from statutory regulations, Ministry of Health workforce reports (2022–2025), and a comparative review of successful retention models from Japan (Jichi Medical University) and Thailand (CPIRD). The analysis reveals that the program is supported by a robust legal foundation and has successfully lowered entry barriers, attracting over 2,278 participants through a centralized digital platform. However, the study identifies a critical structural weakness: the reliance on temporary Non-Civil Servant (Non-ASN) contracts and administrative sanctions creates a transactional "financial bond." This stands in contrast to the "social bond" models utilized in Japan and Thailand, which achieve higher retention through local recruitment and community integration. While the current policy effectively accelerates workforce production, long-term retention remains fragile due to the lack of career security. To ensure sustainability, the policy paradigm must shift from a punitive financial approach to a supportive ecosystem. Recommendations include decentralizing recruitment to create a "rural pipeline" and offering conditional Civil Service (ASN) tracks for graduates committed to long-term service in underserved areas.